Mast cell activation syndrome. Issue 7 (8th July 2021) - Vacheron, Nathalie; McClinton, Tracy; Lynch-Smith, Donna J.; Umberger, Reba
ABSTRACT: Mast cell activation syndrome (MCAS) is a systemic autoinflammatory disease in which mast cells behave erratically. It is unknown whether MCAS recently evolved or if it has been an unrecognized entity for years. Clinically, the patient may present in a constant to near-constant state of allergic reaction. However, the patient may also present with a variety of nonallergic symptoms. There is currently no curative treatment, and providers must prepare to be persistent in seeking symptom-management strategies. This case study describes the vast array of symptoms a typical MCAS patient may exhibit. There is a need for provider education and awareness of this disease that could affect up to 17% of the population on a spectrum from very mild to debilitating symptoms. MCAS is often either misdiagnosed or the diagnosis is greatly delayed due to a lack of provider awareness. Patients may approach primary care providers as their first line of treatment for their aberrant, mysterious symptoms, and therefore it is imperative that nurse practitioners are aware of the disease. Nurse practitioners can play a vital role in the management of MCAS using their attention to detail to recognize patterns, validate patients' experiences, and have a voice in diagnostic criteria consensus.